Efeitos do alagamento e suspensão hídrica na morfologia e fisiologia em plantas jovens de Peltophorum dubium (Spreng) Taubert (Fabaceae). - Lourenço, Luiz Fernando Gonçalves (2023)
Riparian zones are subject to water variations, flooding and drought, altering the characteristics of the environment, which can cause stress in plants that, in response, can alter their morphological and physiological characteristics. With this, we aimed to analyze how: (i) water variations (waterlogging and water suspension) can affect morphological characteristics and their growth? (ii) can they generate changes in chlorophyll and total soluble carbohydrates content? (iii) can physiological characteristics promote plant recovery when returning to field capacity? Peltophorum dubium (Sprengel) Taubert plants were maintained at field capacity (control), waterlogging and water suspension for 15 days, followed by submission to the recovery treatment for 25 days, for morphological, physiological and survival evaluation. Morphological characteristics, growth parameters and chlorophyll and total soluble carbohydrate contents were analyzed; at the end of the experiments, the number of surviving individuals was counted. Waterlogging caused yellowing of leaves and appearance of hypertrophied lenticels and water suspension caused leaf wilting followed by abscission. The stress induced by water suppression negatively affected the fresh and dry biomass of the leaves, stem and root, the number of leaves and the diameter of the stem, in relation to waterlogging the height of the aerial part, fresh biomass of the root, and the diameter of the stem showed significant differences, when compared to the control. Regarding the chlorophyll contents analyzed, only the chlorophyll a/b ratio showed significant differences between the water suspension treatment and the control and waterlogging treatments. The analyses of soluble carbohydrate contents in leaves and roots indicated that the water suspension differed significantly from the control and waterlogging treatments. After the end of the recovery treatment, all post-waterlogging plants survived, while post-water suspension plants showed no signs of recovery. Although waterlogging negatively affected the plants in their leaves and growth parameters, the results indicate that the investigated species has greater tolerance to this type of stress when compared to that subjected to water suspension.